Enhancing Oocyte Competence With Milrinone as a Phosphodiesterase 3A Inhibitor to Improve the Development of Porcine Cloned Embryos - Roy, Pantu Kumar; Qamar, Ahmad Yar; Tanga, Bereket Molla; Fang, Xun; Kim, Ghangyong; Bang, Seonggyu; Cho, Jongki (Frontiers in Cell and Developmental Biology, 2021)
The objective of this study was to investigate the effect of milrinone supplementation as a phosphodiesterase 3A inhibitor during in vitro maturation (IVM) to coordinate the cytoplasmic and nuclear maturation of porcine oocytes and subsequent development of porcine cloned embryos. Brilliant cresyl blue (BCB)-stained (BCB+) oocytes, classified as well-developed, and BCB− oocytes were used in parthenogenesis (PA) and cloning, and their preimplantation development was compared. In PA embryos, BCB+ oocytes had significantly higher rates of development than BCB− oocytes in terms of maturation (87.5 vs. 71.3%), cleavage (88.6 vs. 76.3%), and blastocyst development (34.3% vs. 27.8%) and also had higher cell numbers (46.9% vs. 38.9%), respectively (p < 0.05). In cloned embryos, the BCB+ group also had a significantly higher blastocyst formation rate than the BCB− group (30.6% vs. 20.1%; p < 0.05). Supplementation with 75 µM milrinone during IVM of BCB− oocytes showed improvement in maturation and blastocyst development rates, which may be due to the coordinated maturation of the cytoplasm with the nucleus as an effect of milrinone. Moreover, the analysis of nuclear reprogramming via the examination of the expression levels of the reprogramming-related genes POU5F1, DPPA2, and NDP52IL in milrinone-supplemented BCB− oocytes showed higher expression levels than that in non-treated BCB− oocytes. These findings demonstrate that milrinone is useful in improving developmental competence in less competent oocytes during IVM and for proper nuclear reprogramming in the production of porcine cloned embryos by coordinating cytoplasmic and nucleus maturation.